The Profile of Colonoscopy Examination Results in Surabaya Hajj General Hospital - Hadi Wandono; Iswan Abbas Nusi; Daldiyono Daldiyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: Colonoscopy is the most accurate examination to diagnose abnormalities in ileum terminalis, caecum, colon (ascendent, tranversum and descendent), sigmoid and rectum at present time. The aim of this study was to obtain the profile of colonoscopy examination in Surabaya Hajj General hospital. Method: One hundred and fifty patients who have undergone colonoscopy at Endoscopy Unit of Internal Medicine Department of Surabaya Hajj General Hospital were observed from July 1st, 2008 until October 30th, 2009. Result: There were 87 (58.0%) male and female patients 63 (42.0%) female subjects. Most subjects were at 51-70 years age group of 69 patients (46.0%). The results of colonoscopy examination were as follows: hemorrhoid in 38 subjects (25.3%), colorectal cancer in 32 subject (21.3%), colitis 25 subjects (16.7%), inflammatory bowel disease (IBD) in 15 subjects (10.0%), polyp in 8 subjects (5.3%), diverticulum in 5 subject (3.3%), redundant in 5 subject (3.3%), reduced peristaltic in 3 subject (2.0%), the mass pressure from external colon in 2 subject (1.3%), scybala in 2 subject (1.33%), adhesion in 3 subject (2.0 %), poor/dirty preparation in 6 subject (4.0%) and normal in 6 subject (4.0%). Conclusion: There were four major groups of disease found by colonoscopy in our sunjects including hemorrhoid, colorectal cancer, colitis and IBD. Our study found that colorectal cancer has the greatest number, paticularly the rectosigmoid cancer.   Keywords: colonoscopy, colitis, rectosigmoid, IBD,colorectal cancer